The Impact of Work Environment and Competence on Employee Performance - HA, Ismail (Advances in Human Resource Management Research, 2023)
Purpose: This study aims to empirically examine the impact of the work environment and employee competence on employee performance at the Ministry of Religious Affairs Office in Tana Toraja Regency. The research hypothesizes that both the work environment and competence positively and significantly affect employee performance. Research Design and Methodology: The study employed a saturated sampling method involving all 40 employees from the Ministry of Religious Affairs Office in Tana Toraja Regency. Primary data was collected directly from the respondents through questionnaires. Data analysis included descriptive statistics, validity and reliability tests, and hypothesis testing using multiple linear regression, t-tests, f-tests, and the coefficient of determination. Findings and Discussion: The findings indicate that both the work environment and employee competence positively and significantly affect employee performance, individually and collectively. This suggests that a supportive work environment and high employee competence are crucial for enhancing performance at the Ministry of Religious Affairs Office in Tana Toraja Regency. Implications: The results highlight the importance of fostering a positive work environment and enhancing employee competencies to improve performance. This study provides practical insights for public sector organizations and suggests that future research should explore additional factors and settings to gain a more comprehensive understanding of employee performance determinants.